2022
DOI: 10.1111/apt.17124
|View full text |Cite
|
Sign up to set email alerts
|

TRIM26 inhibits hepatitis B virus replication by promoting HBx degradation and TRIM26 genetic polymorphism predicts PegIFNα treatment response of HBeAg‐positive chronic hepatitis B Patients

Abstract: Summary Background Hepatitis B virus (HBV) infection is a serious global health burden. TRIM26 has been reported to affect hepatitis C virus replication. Aims To manifest the role of TRIM26 on HBV replication and explore if there are single‐nucleotide polymorphisms (SNPs) in TRIM26 associated with response to pegylated interferon‐alpha (PegIFNα) treatment in patients with chronic hepatitis B (CHB). Methods We investigated the effect and mechanism of TRIM26 on HBV replication in vitro. The association between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
(97 reference statements)
0
23
0
Order By: Relevance
“…7 Based on these findings, we elucidated the specific mechanism by how TRIM26 affects HBV replication and demonstrated in two cohorts (Cohort 1, n = 238, Cohort 2, n = 707) that TRIM26 rs116806878 is associated with pegylated interferonα treatment response in patients with HBeAg-positive CHB. 2 We agree with Dr Peng, and mentioned in the discussion section of our original article, that there are still some questions to be explored.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 52%
See 3 more Smart Citations
“…7 Based on these findings, we elucidated the specific mechanism by how TRIM26 affects HBV replication and demonstrated in two cohorts (Cohort 1, n = 238, Cohort 2, n = 707) that TRIM26 rs116806878 is associated with pegylated interferonα treatment response in patients with HBeAg-positive CHB. 2 We agree with Dr Peng, and mentioned in the discussion section of our original article, that there are still some questions to be explored.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 52%
“…We thank Dr Peng for the insightful editorial 1 on our recently published paper. 2 In 2019, about 316 million people had chronic hepatitis B virus (HBV) infection globally. 3 However, HBV infection cannot be eradicated owing to the complexity of the HBV lifecycle.…”
Section: N V I T E D E D I T O R I a Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Luo et al investigated the effect of TRIM26 on HBV replication and the underlying mechanism, and the association between single‐nucleotide polymorphisms (SNPs) in TRIM26 and PegIFNα treatment response in patients with HBeAg‐positive CHB 7 . They demonstrated that TRIM26 inhibited HBV replication by mediating HBx ubiquitination degradation through its SPRY domain and that interferon promoted TRIM26 expression in hepatocellular carcinoma cell lines.…”
mentioning
confidence: 99%